Targeted next-generation sequencing panels for monogenetic disorders in clinical diagnostics: the opportunities and challenges. (January 2015) - de Koning, Tom J; Jongbloed, Jan DH; Sikkema-Raddatz, Birgit; Sinke, Richard J
<x xml:space="preserve">Abstract</x> Next-generation sequencing (NGS) will soon be used for clinically heterogeneous, inherited disorders and the increasing number of disease-causing genes reported. Diagnostic laboratories therefore need to decide which NGS methods they are going to invest in and how to implement them. We discuss here the challenges and opportunities of using targeted resequencing (TRS) panels for diagnosing monogenetic disorders. Of the different NGS approaches available, TRS panels offer the opportunity to sequence and analyze a limited set of predetermined target genes. At present, TRS panels offer better base-pair coverage, running times, costs and dataset handling than other NGS applications such as whole genome sequencing and whole exome sequencing. However, working with TRS panels also poses new challenges in variant interpretation, data handling and bioinformatic analyses. To optimize the analyses, TRS panel testing should be performed by bioinformaticians, clinicians and laboratory staff in close collaboration.